Comparison of Leakage and Quality of Root Canal Filled with Single Cone Technique with Either Bioceramic Sealer or AH Plus Sealer after Post Space Preparation in the Difference Length of Gutta Percha Remaining - Sinkhanarak, Buncha; Wanachantararak, Phenphichar; Sastraruji, Thanapat; Chuveera, Patchanee; Louwakul, Phumisak (Khon Kaen University Dental Journal, 2021)
The aims of this study were to compare the bacterial leakage and to evaluate the obturation quality of root canals filled with single-cone technique using bio ceramic sealer and AH plus sealer after post space preparation with different remaining root canal fillings. Eighty-eight single-rooted mandibular premolars were equally prepared using rotary nickel–titanium files and divided into experimental groups (n=80) positive control group (n=4) and negative control group (n=4). In the experimental groups, all root canals were divided into 2 groups and obturated with single cone technique using either Bio Root RCS (n=40) or AH Plus sealer (n=40) and stored at 37oC for 7 days. The samples in each experimental group were divided into 4 subgroups (n=10) then prepared post space to the remaining apical root canal filling of 1, 2, 3 and 4 mm respectively. Bacterial leakage model using Enterococcus faecalis was employed for 60 days. Then, the apical obturation quality, at 1.5 mm apical root segments, was also evaluated by using a stereomicroscope. The results revealed that, with the remaining apical root canal fillings of 3 and 4 mm, Bio Root RCS group exhibited significantly premature bacterial leakage than AH Plus group (P<0.05), whereas the remaining apical root canal fillings of 1 and 2 mm were no significantly difference between 2 sealers. When compared the quality of the apical root filling at different levels, there was no significant difference in void volume between 2 sealers. At the remaining root canal filling material of 3 and4 mm after post space preparation, Bio root RCS exhibited faster bacterial leakage than AH plus, though the quality of the obturation was not different.